Biosynthesis of Biosurfactant by Pseudomonas aeruginosa Using Cassava Flour Industrial Wastewater as Media - Venty Suryanti; Sri Hastuti; Desi Suci Handayani (ALCHEMY Jurnal Penelitian Kimia, 2014)
Biosynthesis of biosurfactant by Pseudomonas aeruginosa have been prepared using cassava flour industrial wastewater (manipueira) as medium. The optimum condition of the biosurfactans biosynthesis was obtained using media containing nutrient broth and manipueira without centrifugation (NBM) with 4 days fermentation. UV-Vis and FT-IR spectra indicated that the biosurfactant was a rhamnolipid containing hydroxyl, ester, carbocylic and aliphatic carbon chain functional groups. Biosurfactant exhibited critical micelle concentration (CMC) value of 576  mg/L and surface tension value of 0.045  N/m. The biosurfactant was able to decrease the interface tension and form emulsion with benzene, toluene, gasoline and palm oil. This biosurfactant showed w/o emulsion system.